Knocking down LSD1 inhibits the stemness features of colorectal cancer stem cells - Chen,J. (2020)
As a top leading cause of cancer death in many countries, colorectal cancer (CRC) has drawn increasing attention to the study of the pathological mechanism. According to the “cancer stem cell hypothesis”, malignancies originate from a small fraction of cancer cells that show self-renewal properties to initiate and sustain tumor growth and tumor metastasis. Therefore, these cancer stem cells (CSC) probably play important roles in tumor recurrence, metastasis, and drug resistance. Previous research reported that lysine-specific histone demethylase 1 (LSD1) maintains cancer stemness through up-regulating stemness markers SOX2 and OCT4. CD133 is believed to be the most robust surface marker for CRC stem cells, however the regulatory effect of LSD1 on stemness of CD133+ CRC has never been reported. In this study, our objectives included: 1) to isolate pure CD133+ and CD133− cells from SW620 cell line; 2) to investigate the effect of LSD1 on the characteristics of CD133+ stem cancer cells by knocking down the target gene. Results suggested that the SW620 cell line had both CD133+ and CD133− subsets. The CD133+ subset exhibited more CSC-like characteristics compared with the CD133− subset with higher viability, colony formation rate, migration and invasion rate, resistance to anti-cancer drugs, and apoptosis in vitro. The CD133+ also induced faster tumor formation and larger tumors in vivo. In the LSD1-knockdown CD133+ cells, the CSC-like characteristics had been all weakened. We conclude that LSD1 was important for CSCs to maintain their “stemness” features, which could be a potential therapeutic target of CRC.